Good Girls, Bad Girls of the New Testament: Their Enduring Lessons - Wray, T. J. (Rowman & Littlefield Publishers, 2016)
Good Girls, Bad Girls of the New Testament takes readers on a powerful journey through the vast landscape of Roman-occupied Judea during the first century and the genesis of Christianity. This landscape serves as the backdrop for twelve amazing stories of women whose paths intersect, either by providence or design, with the paths of Jesus or Paul. Some of these women are familiar, such as Mary, the mother of Jesus, while others, like the wife of the infamous Pontius Pilate, are lesser known. Whether she is popular or obscure, good or bad, each woman’s story is an important part of the overall Christian narrative. Good Girls, Bad Girls of the New Testament invites readers to take a more nuanced look at twelve stories that feature women, to explore their lives more deeply in historical context, and to understand the real story that includes both men and women. The book goes beyond simply telling the story of a particular biblical woman to challenge readers to explore the enduring lessons the ancient writers sought to impart. These timeless lessons are as important for us today as they were thousands of years ago.